2007
DOI: 10.1002/jsfa.2934
|View full text |Cite
|
Sign up to set email alerts
|

Moisture profile determination in urea prill. I

Abstract: Using Karl Fischer titration, the moisture profile along the radius in urea prill was determined. Having verified that during dissolution in methanol the urea grains diminish in radius linearly with time, it was possible to calculate that the layer with the highest water content is at a depth of one-third of the radius. The moisture profile is linear, with the central moisture content equal to four times the global moisture content of the grain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In a previous study, 8 using KF titrations, the linear moisture profile in urea prill was determined experimentally. The obtained data show that the moisture content is zero at the surface and increases towards the interior, reaching a maximum (four times greater than the global moisture content) in the centre.…”
Section: Conclusion and Consequencesmentioning
confidence: 99%
See 3 more Smart Citations
“…In a previous study, 8 using KF titrations, the linear moisture profile in urea prill was determined experimentally. The obtained data show that the moisture content is zero at the surface and increases towards the interior, reaching a maximum (four times greater than the global moisture content) in the centre.…”
Section: Conclusion and Consequencesmentioning
confidence: 99%
“…In order to determine the function V KF = f (t), we have previously demonstrated that the water mass detected by the burette in a time interval dt comes solely from the dissolution of a concentric layer of urea grains of thickness dr. 8 The urea mass in this layer is dm = 4πρr 2 dr(g)…”
Section: Appendixmentioning
confidence: 99%
See 2 more Smart Citations